Jerusalem Unbound - Muhammad Yaseen Gada (International Institute of Islamic Thought, 2015)
Jerusalem represents the heart of the Israeli-Palestinian conflict. The everchanging events there have perplexed and compelled analysts, political scientists, academics, and activists to devise countless solutions, especially since 1948. Moreover, the last decade has witnessed a substantial change in its demography due to the Separation Wall and the ongoing Jewish settlement in East Jerusalem, both of which violate international law and agreements. The physical barrier is itself a grim reminder of Israel’s harsh unilateral and discriminatory measures that seriously impact for the bilateral peace process. Michael Dumper (professor of Middle East politics, University of Exeter) has written extensively on the Israeli-Palestinian conflict. In this book, he explores and illustrates how, despite the wall (hard border), people on the both sides have managed to create and retain various trans-wall spheres of influence (soft borders) by taking advantage of its porous nature to breach it by various ways. This reality, which renders Jerusalem a “many-bordered” or unbound city, is primarily attributable to its rich, complex, and intersecting religious and political interests that are sought and contested by many actors (p. 5). The city’s physical boundaries, discussed in chapter 1, shifted continuously from 1947 to 2003; the Separation Wall actually runs right through it. According to Dumper, three major events have had long-term ramifications on this conflict: the 1947 UN Partition Plan; the 1949 partition of East and West Jerusalem between Jordan and Israel, respectively; and the ongoing illegal Israeli ...